G. R. Beasley-Murray and the Book of Revelation - Woodman, Simon (2025)
This article marks the 50th anniversary of G. R. Beasley-Murray’s New Century Bible Commentary on the Book of Revelation, examining its theological and scholarly significance. Beasley-Murray’s approach integrates historical-critical methods with a faith-oriented perspective, demonstrating how John’s use of first-century Jewish and Greco-Roman imagery serves to articulate theological truth. Situated at the intersection of biblical scholarship, pastoral theology, and apologetics, his commentary exemplifies a rare synthesis of academic rigour and ecclesial relevance. This study reassesses the enduring influence of Beasley-Murray’s work, considering its contribution to both contemporary theological discourse and the practice of ministry.
Keywords: Eschatology; historical-critical method; Book of Revelation; Biblical Scholarship; Apologetics; G. R. Beasley-Murray